2021
DOI: 10.3390/ph14070628
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of DNA Demethylases in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancers (TNBCs) are very heterogenous, molecularly diverse, and are characterized by a high propensity to relapse or metastasize. Clinically, TNBC remains a diagnosis of exclusion by the lack of hormone receptors (Estrogen Receptor (ER) and Progesterone Receptor (PR)) as well as the absence of overexpression and/or amplification of HER2. DNA methylation plays an important role in breast cancer carcinogenesis and TNBCs have a distinct DNA methylation profile characterized by marked hypome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The role of TET1 in breast cancer is controversial. While some studies indicated that TET1 is a tumor suppressor gene ( 20 , 21 ), others demonstrated that it is an oncogene ( 16 , 32 ). In the current study our results indicate that the picture seems to be more complicated and that the role of TET1 in breast cancer is not black and white.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TET1 in breast cancer is controversial. While some studies indicated that TET1 is a tumor suppressor gene ( 20 , 21 ), others demonstrated that it is an oncogene ( 16 , 32 ). In the current study our results indicate that the picture seems to be more complicated and that the role of TET1 in breast cancer is not black and white.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dysregulation of DNA methylation can promote or maintain the cancer cell stemness, thereby contributing to the pathogenesis of BC [ 8 , 9 ]. Moreover, TNBC patients exhibited widespread genomic hypomethylation, while the buildup of methylation enhanced the risk of BC in postmenopausal women [ 10 , 11 ]. In addition, dysregulation of histone modification also serves as a crucial marker in cancer [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%